2021
DOI: 10.3390/cancers13143574
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Major Differences in Sex- and Age-Specific Diagnostic Performance among Nine Faecal Immunochemical Tests Used for Colorectal Cancer Screening

Abstract: Evidence on diagnostic performance of faecal immunochemical tests (FITs) by sex and age is scarce. We aimed to evaluate FIT performance for detection of advanced colorectal neoplasia (AN) by sex and age across nine different FIT brands in a colonoscopy-controlled setting. The faecal samples were obtained from 2042 participants of colonoscopy screening. All eligible cases with AN (n = 216) and 300 randomly selected participants without AN were included. Diagnostic performance for detection of AN was assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The NPV of a negative result in the four biomarkers for the diagnosis of significant pathology was higher in females (97.3% vs 91.9% in males) and in younger patients (98.5% in patients under 50 years old vs 93% in older patients). This better performance of the faecal test in women and younger patients has been previously reported in similar studies [41]. A triage strategy based in the POC test would have avoided 36.8% (210/571) of colonoscopies without missing any CRC or IBD case.…”
Section: Discussionsupporting
confidence: 75%
“…The NPV of a negative result in the four biomarkers for the diagnosis of significant pathology was higher in females (97.3% vs 91.9% in males) and in younger patients (98.5% in patients under 50 years old vs 93% in older patients). This better performance of the faecal test in women and younger patients has been previously reported in similar studies [41]. A triage strategy based in the POC test would have avoided 36.8% (210/571) of colonoscopies without missing any CRC or IBD case.…”
Section: Discussionsupporting
confidence: 75%
“… 54 55 Most are qualitative with the positivity threshold set by the manufacturer and have not been subjected to large population studies, 56 but several are quantitative, allowing for adjustment of the positivity threshold, and have been extensively studied. 57–59 …”
Section: Explanatory Text For Each Principlementioning
confidence: 99%
“…54 55 Most are qualitative with the positivity threshold set by the manufacturer and have not been subjected to large population studies, 56 but several are quantitative, allowing for adjustment of the positivity threshold, and have been extensively studied. [57][58][59] Setting analytical specifications of a new test where the technology incorporates new biomarkers or biomarker combinations will initially depend very much on phases I and II evaluations, where positivity criteria are usually based on the combination that best discriminates between CRC and non-CRC states. Typically, these generate diagnostic sensitivities that are not maintained in validation studies undertaken in phase III studies (typical screening populations) and positivity thresholds might need adjustment.…”
Section: Explanatory Textmentioning
confidence: 99%
“…The reason for the lower FIT in women is unclear but could be related to a higher rate of lesions in the proximal colon that are less prone to bleeding or a longer colonic transit time in women, leading to a larger degree of fecal hemoglobin degradation. [10][11][12][13] If the lower FIT in women was due to obstipation, the gender difference would be greater in CRCs in the proximal colon than in distal segments. On the contrary, a study from the Scottish bowel screening program showed significantly lower FIT levels in women only in the left-sided CRCs.…”
Section: Introductionmentioning
confidence: 99%